Agronomic characteristics of sorghum genotypes and nutritional values of silage - Costa, Renê Ferreira; Pires, Daniel Ananias de Assis; Moura, Marielly Maria Almeida; Sales, Eleuza Clarete Junqueira de; Rodrigues, José Avelino Santos; Rigueira, João Paulo Sampaio (Acta Scientiarum. Animal Sciences, 2016)
The objective was to assess agronomic characteristics of sorghum genotypes and nutritional values of produced silage. A total of 15 sorghum genotypes were used. Planting was carried out through a randomized-block design with three replications per genotype, totaling forty-five (45) plots. Agronomic and nutritional characteristics, besides the quality of the silage, were assessed. There were differences between genotypes for all characteristics analyzed, with the exception of levels of acid detergent unavailable nitrogen (ADUN), acid detergent unavailable protein (ADUP) and water activity (aw). The assessment of the parameters, except for genotypes 1016013, 1016025, 1016037, 1016039, Volumax and BRS 610, which presented protein level below 7%, showed that the other genotypes can be used for silage production, since they have a good profile of fermentation and in vitro dry matter digestibility; however, genotype SF15 is the most favorable one for silage production due to its little participation in the neutral detergent fiber fraction.